Towards a model for incorporating peace education in South African higher education - Ndwandwe, N. D. (South African Journal of Higher Education, 2024)
Peace education is the basis for global peace and a prerequisite for attaining sustainable development and global goals. Considering the widespread physical and structural violence and destructive protests across South African higher education, it is crucial to embrace peace education to deal with violence in all its forms. This article explores the need for peace education in the South African higher education curriculum. A qualitative critical review of the literature reveals widespread gender-based violence, sexual exploitation, destructive student protests at and the militarisation of universities through military force to quell violent student protests nationwide in South Africa. Lack of peace skills indicates that both lecturers, university management and students are in need peace education. Peace education must be incorporated in South African higher education. As part of a model for it, this article recommends the establishment of peace as a stand-alone subject, extra-curricular activities for peace and storytelling to deliver peace education and inculcate a culture of peace in both educators and students. More so, there is a need to embrace the pedagogy of peace education and establish institutes for peace and conflict resolution at every higher education institution in South Africa.